Cyrtodactylus rosichonariefi sp. nov. (Squamata: Gekkonidae), a new swamp-dwelling bent-toed gecko from Bunguran Island (Great Natuna), Indonesia - Riyanto, Awal; Grismer, L. Lee; Wood, Perry L.jr. (Zootaxa, 2015)
Cyrtodactylus rosichonariefi sp. nov. is the second newly described species of Bent-toed gecko from Bunguran Island (Great Natuna), Indonesia. This species occurs in the Sekunyam Forest and is differentiated from all other species of the C. semenanjungensis species group of the Thai-Malay Peninsula by having the following unique combination of characteristics: intermediate size (SVL of adult male holotype 54.6 mm); enlarged femoral scales, femoral pores, no precloacal groove, enlarged precloacal scales, no precloacal pores; subcaudals not enlarged; and dorsal pattern blotched but lacking paired, dark, semilunar-shaped blotches on upper nape. The new species is the sister species of C. majulah Grismer, Wood & Lim.